Comparison of two hybrid algorithms on incorporated aircraft routing and crew pairing problems - Nurul Farihan Mohamed (Tanjong Malim, 2020)
Comparison of two hybrid algorithms on incorporated aircraft routing and crew pairing problems by Nurul Farihan Mohamed